Determining the Difficulties Experienced by Patients in Activities of Daily Living After Appendectomy: A Prospective Observational Study - Hülya Bulut; Gamze Bozkul (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: Appendectomies are among the most frequently performed emergency surgicalprocedures and patients often encounter difficulties in performing activities of daily living.Aim: The aim of this study was to determine the difficulties experienced by patients after appendectomy.Method: A total of 60 patients who underwent an appendectomy were included in the study wasconducted. The data of the study were collected using Personal Information Form and the Effect ofthe Surgery on the Patients’ Daily Life Activities form. Descriptive statistical methods, Mann WhitneyU, and Friedman tests were used to evaluate the data.Results: After appendectomy surgery, patients experienced difficulties in performing activities of dailyliving and these difficulties were higher in the first two weeks but decreased statistically significantlyover time (p lt; 0.05). Postoperative nausea and vomiting 0.53 ± 1.2, pain during mobilization 4.07± 1.41, loss of appetite 0.7 ± 1.26, discomfort at the wound site 1.47 ± 1.78, and the desire to hidethe wound 0.4 ± 1.07 were more common in the female patients than in the male patients afterthe appendectomy. In addition, patients who underwent open appendectomy experienced morepostoperative difficulty (p lt; 0.05).Conclusion: From the results of the study, the patients undergoing appendectomy experienceddifficulties. It is recommended that patients who have undergone an appendectomy be followed upby phone and provided counseling after discharge in order to prevent the potential difficulties theymay experience.